Stock market interactions and the impact of macroeconomic news: Evidence from high frequency data of European futures markets - Bea Canto; Roman Kräussl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2006)
This study analyzes the short-term dynamic spillovers between the futures returns on the DAX, the DJ Eurostoxx 50 and the FTSE 100. It also examines whether economic news is one source of international stock return co-movements. In particular, we test whether stock market interdependencies are attributable to reactions of foreign traders to public economic information. Moreover, we analyze whether cross-market linkages remain the same or whether they do increase during periods in which economic news is released in one of the countries. Our main results can be summarized as follows: (i) there are clear short term international dynamic interactions among the European stock futures markets; (ii) foreign economic news affects domestic returns; (iii) futures returns adjust to news immediately; (iv) announcement timing of macroeconomic news matters; (v) stock market dynamic interactions do not increase at the time of the release of economic news; (vi) foreign investors react to the content of the news itself more than to the response of the domestic market to the national news; and (vii) contemporaneous correlation between futures returns changes at the time of macroeconomic releases.
urn:nbn:de:hebis:30-37992
Keywords: G14; G15; 330; Market Microstructure; Stock Market Dynamic Interactions; Macroeconomic News; High Frequency Data; VAR Modeling; Variance Decomposition